Underground Adaptation to a Hostile Environment: Acute Myeloid Leukemia vs. Natural Killer Cells - Dulphy, Nicolas; Chrétien, Anne-Sophie; Khaznadar, Zena; Fauriat, Cyril; Nanbakhsh, Arash; Caignard, Anne; Chouaib, Salem; Olive, Daniel; Toubert, Antoine (Frontiers in Immunology, 2016)
Acute myeloid leukemia (AML) is a heterogeneous group of malignancies which incidence increases with age. The disease affects the differentiation of hematopoietic stem or precursor cells in the bone marrow and can be related to abnormal cytogenetic and/or specific mutational patterns. AML blasts can be sensitive to natural killer (NK) cell anti-tumor response. However, NK cells are frequently defective in AML patients leading to tumor escape. NK cell defects affect not only the expression of the activating NK receptors, including the Natural Cytotoxicity Receptors (NCR), the NK group 2, member D (NKG2D) and the DNAX accessory molecule-1 (DNAM-1), but also cytotoxicity and IFN-g release. Such perturbations in NK cell physiology could be related to the adaptation of the AML to the immune pressure and more generally to patient's clinical features. Various mechanisms are potentially involved in the inhibition of NK-cell functions in AML including defects in the normal lymphopoiesis, reduced expression of activating receptors through cell-to-cell contacts, and production of immunosuppressive soluble agents by leukemic blasts. Therefore, the continuous cross-talk between AML and NK cells participates to the leukemia immune escape and eventually to patient's relapse. Methods to restore or stimulate NK cells seem to be attractive strategies to treat patients once the complete remission is achieved. Moreover, our capacity in stimulating the NK cell functions could lead to the development of preemptive strategies to eliminate leukemia-initiating cells before the emergence of the disease in elderly individuals presenting pre-leukemic mutations in hematopoietic stem cells.